A Study of the Principal’s Leadership Role on Teacher’s Performance in Tonra State Senior High School 1, Bone Regency of the South Sulawesi Province, Indonesia. - Yunus, Andi Muhammad; Nurman; illahi, Rahmat; Kamaruddin; Alimuddin (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
This study was conducted to determine the effect of the Principal’s leadership role on teacher’s performance, as well as an analysis of the teacher’s performance at the Tonra 1 Tonra District Bone School Bone Regency of the South Sulawesi Province, Indonesia. In conducting this research, samples were gathered with the non-probalitas data collection sample. Questionnaires, documentation, and interviews were also other method used. Descriptive and correlation techniques were used to analysis the collected data. The results showed that the principal’s leadership role towards the school teachers is democratic in nature. Data analyzed showed that the principal is always known for paying attention to the teacher’s welfare and school development. The teacher’s performance description is rated satisfactory. This is because of the level of discipline exhibited by the school teachers during working hours, their high level of preparation with learning tools, and the implementation and completion of school activities. Thus, the school principal’s high leadership skill affects the teacher’s productivity which in turn helped increase the quality of education.